2017
DOI: 10.1128/jvi.02261-16
|View full text |Cite
|
Sign up to set email alerts
|

Two White Spot Syndrome Virus MicroRNAs Target the Dorsal Gene To Promote Virus Infection in Marsupenaeus japonicus Shrimp

Abstract: In eukaryotes, microRNAs (miRNAs) serve as regulators of many biological processes, including virus infection. An miRNA can generally target diverse genes during virus-host interactions. However, the regulation of gene expression by multiple miRNAs has not yet been extensively explored during virus infection. This study found that the Spaztle (Spz)-Toll-Dorsal-antilipopolysaccharide factor (ALF) signaling pathway plays a very important role in antiviral immunity against invasion of white spot syndrome virus (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 47 publications
(36 reference statements)
2
28
0
Order By: Relevance
“…By RNAi method, we observe that shrimps with knockdown of Dorsal have elevated viral loads than those of the GFP control group, suggesting that Dorsal is important for host to limit viral replication. Besides, the report of WSSV encoding two MicroRNAs with the ability to suppress shrimp Dorsal also supports that Dorsal is a key restrict factor against viral infection (56). However, knockdown of Dorsal results in lower viral loads than those of MyD88, Tube and Pelle silenced groups, which may be explained by that Dorsal locates the lower levels at MyD88/Tube/Pelle cascade of the canonical Toll pathway.…”
Section: Discussionmentioning
confidence: 80%
“…By RNAi method, we observe that shrimps with knockdown of Dorsal have elevated viral loads than those of the GFP control group, suggesting that Dorsal is important for host to limit viral replication. Besides, the report of WSSV encoding two MicroRNAs with the ability to suppress shrimp Dorsal also supports that Dorsal is a key restrict factor against viral infection (56). However, knockdown of Dorsal results in lower viral loads than those of MyD88, Tube and Pelle silenced groups, which may be explained by that Dorsal locates the lower levels at MyD88/Tube/Pelle cascade of the canonical Toll pathway.…”
Section: Discussionmentioning
confidence: 80%
“…Firstly, miRNA was found to have a profound effect on the expression pattern of several hundred mRNAs (Reddy, 2015). One miRNA may target and regulate multiple genes, and one gene can be regulated by multiple miRNA (Qian et al, 2017). For example, several miRNAs in EBV cluster 1 have been identified to show both pro-apoptotic and anti-apoptotic effects (Vereide et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that virus-encoded miRNAs influence virus replication and propagation. Viral miRNAs are expressed during infection, suggesting that viral miRNA might participate in virus propagation and survival (Qian et al, 2017). For example, WSSV-miR-N24 inhibits cell apoptosis through increase in caspase 8 expression, leading to an increase in WSSV copy number (Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, the results showed that the host and viral miRNAs could inhibit the expressions of DCP1 and DCP2 during DNA virus infection. MiRNAs, a large class of small noncoding RNAs in diverse eukaryotic organisms, are sequentially processed by two RNase III proteins, Drosha and Dicer from the stem regions of long hairpin transcripts (28, 37). The mature miRNA strand is liberated from the miRNA:miRNA* duplex and integrated into the RNA induced silencing complex (RISC), and inhibits the expression of cognate mRNA through degradation or translation repression in the RISC (18).…”
Section: Discussionmentioning
confidence: 99%